Olive oil and haemostasis - Colette N.M. Kelly; George J. Miller; Christine M. Williams (Grasas y Aceites, 2004)
Olive oil is a key component of the traditional Mediterranean diet; a diet that may explain the low rate of cardiovascular disease (CVD) in Southern European. (Extra virgin) Olive oil is a good source of monounsaturated fatty acids (MUFA) and phenolic compounds, both of which have been investigated for their effects on plasma lipids and lipoproteins, measures of oxidation and factors related to thrombosis. This issue aims to summarise the current understanding of the effects of such dietary components on the haemostatic system and subsequent risk of CVD. To date, evidence suggests that diets rich in MUFA and thus in olive oil attenuate the thrombotic response via a reduction in platelet aggregation and in postprandial FVII levels. Thrombosis is a key event in causing heart attacks and strokes, which if modulated by diet could pose a cost-effective way of reducing CVD incidence in populations that adhere to MUFA/olive oil-rich diets long-term.